(untitled) (Karya Ilmiah Mahasiswa (KIMA), 2022)
Writing is the ways to express thoughts to the reader in the form of written. Writing is a skill that is required in written communication. By writing, students can use explore their idea in writing form. A good writing is not always easy and may be a challenge even for the best students. One of the learning strategies of writing is the Think-Talk-Write (TTW) strategy. This strategy is used to develop an effective and efficient learning system. The purpose of this research was to determine the improvement of students writing ability after being taught through Think-Talk-Write Strategy. The research sample was Class XI of SMAN 2 Totikum and the number of which was collected using random sampling techniques as many as 20 students in class XI IPA. Pre-experimental method was applied in this research with one group pre-test and post-test design. The instrument used to collect data was writing test and the components of writing that measured were grammar and vocabulary and the study lasted for five weeks. The result of pre-test was 64.5 it was indicated in fair score classification and the mean score of students’ post-tests was 83.25 it was indicated in good score classification. The standard deviation of pre-test was 6.262 and the standard deviation of post- test was 7.122. This is supported by the significant t-test value is less than 0.05 (0.00 < 0.05). Therefore, the Alternative hypothesis was accepted and the Null Hypothesis was rejected. Test scores are significant improvement, so the researcher suggests that Think-Talk-Write strategy may be used as alternative media in teaching writing.